A Study on Obesity and its Risk Factors Associated with Mizaj (Temperament) of the Person in Maharu Village, Grama Niladhari Division, Kinniya, Trincomalee - Zeenath, A.L.A.; Shiffa, M.; Fahamiya, N. (Faculty of Indigenous Medicine, University of Colombo, 2025)
Obesity is an increasing health issue because it causes significant adverse health effects among adults. The objective of this survey is to explore the association between obesity and its risk factors in obese individual in Maharu Village, Grama Niladhari Division; Kinniya, Trincomalee, situated in the Eastern Province of Sri Lanka. A community-based cross-sectional survey was conducted among 206 individuals (BMI >30), selected through random sampling. Data were collected using a structured questionnaire following ethical approval (ERC Reference: 24/303). The age of participants ranged from 25 to 76 years, with females comprising the majority (72%) and males 28%. The mean BMI value of the participant is 33.2 with standard deviation of 2.56. Analysis of temperament revealed that 54.4% of participants had Balghami Mizaj, 44.7% had Damavi Mizaj, while the rest were classified as Safravi or Saudavi. The majority of participants reported poor dietary habits and a lack of physical activity, both of which are recognized contributors to obesity. Findings suggest that individuals with Balghami Mizaj may be more susceptible to obesity compared to other temperaments. The study highlights the influence of unhealthy lifestyles and dietary behaviors in the development of obesity. These insights underline the need for targeted preventive strategies and health education programs focused on promoting healthier lifestyle choices at the community level to combat the rising obesity epidemic
Keywords: Risk factors; Mizaj; BMI; Balghami Mizaj; Obesity